Eine relationale Perspektive auf Lernen Ontologische Hintergrundsannahmen in lerntheoretischen Konzeptualisierungen des Menschen und von Sozialität - Schaller, Franz (Verlag Barbara Budrich, 2012)
What can learning mean? Different approaches to learning theory represent a "relational view". The ontological premises, however, remain implicit. Thus, these approaches leave their conceptualizations of the human being and of sociality to an intuitive understanding of the background. The obvious conceptualization of the human being as an "open personality" or as a "homines aperti" (N. Elias) and of sociality as an inherent sociality of the learner or "primary sociality" (H. Joas) thus receives insufficient "ontological support".